Effect of Zinc Supplementation on Maintenance Hemodialysis Patients: A Systematic Review and Meta-Analysis of 15 Randomized Controlled Trials. (31st December 2017) - Wang, Ling-Jun; Wang, Ming-Qing; Hu, Rong; Yang, Yi; Huang, Yu-Sheng; Xian, Shao-Xiang; Lu, Lu
Abstract : We aimed to examine the effects of zinc supplementation on nutritional status, lipid profile, and antioxidant and anti-inflammatory therapies in maintenance hemodialysis (MHD) patients. We performed a systematic review and meta-analysis of randomized, controlled clinical trials of zinc supplementation. Metaregression analyses were utilized to determine the cause of discrepancy. Begg and Egger tests were performed to assess publication bias. Subgroup analysis was utilized to investigate the effects of zinc supplementation in certain conditions. In the crude pooled results, we found that zinc supplementation resulted in higher serum zinc levels (weighted mean difference [WMD] = 28.489; P < 0.001 ), higher dietary protein intake (WMD = 8.012; P < 0.001 ), higher superoxide dismutase levels (WMD = 357.568; P = 0.001 ), and lower levels of C-reactive protein (WMD = −8.618; P = 0.015 ) and malondialdehyde (WMD = −1.275; P < 0.001 ). The results showed no differences in lipid profile. In the metaregression analysis, we found that serum zinc levels correlated positively with intervention time (β = 0.272 ; P = 0.042 ) and varied greatly by ethnicity (P = 0.023 ). Results from Begg and Egger tests showed that there was no significant bias in our meta-analysis (P > 0.1 ). Results of subgroup analysis supported the above results. Our analysis shows that zinc supplementation may benefit the nutritional status of MHD patients and show a time-effect relationship.